Mixed patterns of morphological adaptation to insularity in an aerial displaying bird, the Common Snipe Gallinago gallinago. (31st January 2018) - Rodrigues, Tiago M.; Andrade, Pedro; Rodrigues, Marisa; Gonçalves, David
Abstract : On islands, colonizing birds may evolve behavioural and morphological adaptations to the new environment, often resulting in changes in body size and reduction or even total loss of flight. These island populations have therefore been used to test hypotheses related to adaptations for flight. However, in certain species in which flight is used not only in foraging and migration but also in mating displays, disentangling the effects of natural and social selection is difficult. Thus, sedentary populations of species that perform aerial displays (such as the Common Snipe Gallinago gallinago that breed in the Azores archipelago) may offer an opportunity to separate the effects of natural and social selection on morphology. If insular Common Snipe respond to the characteristic ecological context of oceanic islands, we expect them to differ from migratory conspecifics in body size and by having relatively smaller and more rounded wings. On the other hand, if social selection exerts a more powerful force over the morphology of this species, we expect that sedentary and migratory birds will not differ in flight‐related characters. We tested these hypotheses by comparing morphological characters measured on live Common Snipe captured in the Azores during the breeding season with those measured on migratory specimens hunted during autumn/winter in mainland Portugal. Sedentary Azorean birds were smaller and had relatively shorter tails but did not show the tendency for insular birds to possess more rounded wings as described in other taxa, including in the Azores. Bergman's rule might explain the difference in body size and shorter tails may be responsible for behavioural differences between populations. The lack of difference in wing shape might be explained by the need of the Common Snipe to perform aerial displays during courtship, suggesting an effect of social selection on the migratory strategy of this species.